Recycling Coal Fly Ash for Super-Thermal-Insulating Aerogel Fiber Preparation with Simultaneous Al2O3 Extraction - Jie Gu; Lipeng Liu; Rongrong Zhu; Qiqi Song; Hanqing Yu; Pengjie Jiang; Changqing Miao; Yuxiang Du; Rui Fu; Yaxiong Wang; Yan Hao; Huazheng Sai (Molecules, 2023)
A large quantity of coal fly ash is generated worldwide from thermal power plants, causing a serious environmental threat owing to disposal and storage problems. In this work, for the first time, coal fly ash is converted into advanced and novel aerogel fibers and high-purity α-Al2O3. Silica–bacterial cellulose composite aerogel fibers (CAFs) were synthesized using an in situ sol-gel process under ambient pressure drying. Due to the unique “nanoscale interpenetrating network” (IPN) structure, the CAFs showed wonderful mechanical properties with an optimum tensile strength of 5.0 MPa at an ultimate elongation of 5.8%. Furthermore, CAFs with a high porosity (91.8%) and high specific surface area (588.75 m2/g) can inherit advanced features, including excellent thermal insulation, stability over a wide temperature range, and hydrophobicity (contact angle of approximately 144°). Additionally, Al2O3 was simultaneously extracted from the coal fly ash to ensure that the coal fly ash was fully exploited. Overall, low-cost woven CAFs fabrics are suitable for wearable applications and offer a great approach to comprehensively use coal fly ash to address environmental threats.